2002
DOI: 10.1067/mhn.2002.125756
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Laryngeal Collagen Augmentation for Treatment of Parkinsonian Hypophonia

Abstract: Percutaneous laryngeal collagen augmentation is an effective treatment for parkinsonian hypophonia in a majority of patients. Patients with advanced neurologic disease with aphonia, difficulty with speech initiation, dysphagia, or ambulatory difficulty are less likely to respond to this procedure and should be so informed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
(28 reference statements)
2
13
0
2
Order By: Relevance
“…Increasing vocal fold thickness ͑and therefore also reducing glottal rest area͒ by injection of collagen has resulted in subjective improvement in the quality of speech among patients with Parkinson's disease. [48][49][50] Extending our analysis to another physiological parameter, vocal fold thickness, provides an opportunity for evaluation of another important determinant of properties of phonation. It has been clinically found that in comparison with R treatment, the LSVT is more effective at increasing sound pressure level and reducing the breathy voice.…”
Section: -6mentioning
confidence: 99%
“…Increasing vocal fold thickness ͑and therefore also reducing glottal rest area͒ by injection of collagen has resulted in subjective improvement in the quality of speech among patients with Parkinson's disease. [48][49][50] Extending our analysis to another physiological parameter, vocal fold thickness, provides an opportunity for evaluation of another important determinant of properties of phonation. It has been clinically found that in comparison with R treatment, the LSVT is more effective at increasing sound pressure level and reducing the breathy voice.…”
Section: -6mentioning
confidence: 99%
“…Because of the small needle caliber, injection can be performed without the need for local cutaneous anesthetic, let alone intravenous sedation. Percutaneous injection laryngoplasty using collagen affords a safe route to medialization even in the most debilitated patient population, such as in patients with Parkinsonian hypophonia 7, 8. The Point‐Touch technique is now used in the treatment of a variety of laryngeal disorders, including vocal fold paralysis, spasmodic dysphonia, and vocal fold granuloma 6, 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic Parkinson's disease (IPD) is a progressive neuromuscular disorder that affects nearly 2 million Americans 1 . In addition to the hallmark symptoms of tremor, rigidity, and bradykinesia, 2 IPD has significant and progressive manifestations in the phonatory system that frequently result in debilitating communicative deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Of the nearly 2 million Americans with IPD, 70% to 90% of patients exhibit some form of Parkinson's‐related dysphonia (PRD) 2–5 . Nearly one third of these patients cite dysphonia as their most debilitating deficit 1,3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation